PP.28.12: GENE EXPRESSION OF ENAC-ALPHA, NA+/K+-ATPASE-ALPHA/-BETA AND THE MINERALOCORTICOID RECEPTOR IS AFFECTED BY INHIBITION OF SOLUBLE ADENYLYL CYCLASE IN THE VASCULAR ENDOTHELIUM. (June 2015) - Nedele, J.; Schmitz, B.; Guske, K.; Maase, M.; Lenders, L.; Schelleckes, M.; Kusche-Vihrog, K.; Brand, S.-M.; Brand, E.
Abstract : Objective: Components of the Renin-Angiotensin-Aldosterone-System (RAAS) are expressed and regulated in vascular endothelial cells. In particular, the epithelial Na+-channel (ENaC), the mineralocorticoid receptor (MR), and the Na+/K+-ATPase have been reported to regulate endothelial stiffness in response to serum Na+. In the current work, we determined the effect of sAC inhibition on endothelial stiffness. Furthermore, we analyzed sAC-dependent CRE-mediated transcriptional activation and the effects of sAC inhibition on ENaC-α, Na+/K+-ATPase-α/-β and MR expression on mRNA and protein levels. Design and method: We determined the contribution of sAC to transcriptional activation in vascular endothelial cells (EC) and kidney collecting duct cells. Inhibition of sAC by the specific inhibitor KH7 reduced CRE-mediated promoter activity via reduction of CREB phosphorylation. KH7 and anti-sAC siRNA decreased mRNA and protein levels of ENaC-α and Na+/K+-ATPase-α. In Chromatin Immunoprecipitation (ChIP) experiments, sAC-dependent changes of CREB-p binding at ENaC and Na+/K+-ATPase-α promoter regions were analyzed. Using atomic force microscopy (AFM), a nano-technique that measures stiffness and deformability of living cells, we detected endothelial cell softening in mice aortae after sAC inhibition. Results: Pharmacological inhibition of sAC by KH7 significantly decreased transcriptional activity of the CRE control vector (p < 0.05). In addition, phosphorylated CREB was significantly reduced after KH7 treatment (p < 0.05), whereas unphosphorylated CREB remained unaffected. Inhibition of sAC by KH7 and siRNA reduced expression of ENaC-α, Na+/K+-ATPase-α1/β1 and sAC (all p values < 0.012). Additionally, sAC inhibition by siRNA decreased ENaC-α and Na+/K+-ATPase-α protein levels (all p values < 0.05). ChIP experiments in ECs revealed binding of CREB-p to ENaC-α and Na+/K+-ATPase-α promoters under basic conditions which was prevented by sAC inhibition. AFM measurements revealed that KH7-treated mouse aorta ECs were significantly softer than untreated cells and aldosterone-induced stiffening of mouse aorta ECs was prevented by sAC inhibition (all p-values < 0.05). Conclusions: Selective sAC inhibition prevents aldosterone-induced endothelial stiffening. The underlying mechanism involves gene expression regulation of ENaC-α and Na+/K+-ATPase-α1 and -β1. Additional studies are warranted to investigate the protective action of sAC inhibitors in humans for potential clinical use.